Recurrent Massive Epistaxis from an Anomalous Posterior Ethmoid Artery - Marco Giuseppe Greco; Francesco Mattioli; Maria Paola Alberici; Livio Presutti (Case Reports in Otolaryngology)
A 50-year-old man, with no previous history of epistaxis, was hospitalized at our facility for left recurrent posterior epistaxis. The patient underwent surgical treatment three times and only the operator’s experience and radiological support (cranial angiography) allowed us to control the epistaxis and stop the bleeding. The difficult bleeding management and control was attributed to an abnormal course of the left posterior ethmoidal artery. When bleeding seems to come from the roof of the nasal cavity, it is important to identify the ethmoid arteries always bearing in mind the possible existence of anomalous courses.